Literary Characters as a Source Domain of Precedent Names in the UK Media - E. V. Budaev (Научный диалог)
The article deals with precedent names (PN) from the source domain “Literature”, functioning in the UK media. The material for the study was 104 examples of precedent names used in the British print media (The Guardian, The Times, The Daily Mail, The Daily Telegraph, The Independent) over the past ten years (2010–2019). Research methods were cognitive-discourse analysis, linguocultural description. It is concluded that the source domain “Literary characters” is the most demanded source of precedent names in the British media (26 % of the total body of examples, which is 400 precedent names).  It is shown that British journalists give preference to onyms related to British literature, which is natural, because PN data are well known to both journalists and British media addressees. It was revealed that British journalists regularly refer to the names of characters from the classics of English literature in their texts. At the same time, it is shown that the leading place in terms of frequency of actualization and productivity is occupied by PN, which have become popular in recent decades, which primarily refers to the characters of J. Rowling's Harry Potter novels. Thus, the analysis showed that the functioning of PN depends not only on cognitive and cultural, but also on discursive factors.